Absence/silence of a translation as a borderline issue: Şeytan Ayetleri (The Satanic Verses) - Yılmaz, Sevcan. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
This thesis is particularly concerned with what the effects of ideology on the selection process of the translation are and how and why ideology aborts authors or texts-to-be-translated. Firstly, the significance of silence and absence in general is stressed to explain the reasons of analyzing a book which has not been translated into Turkish: Salman Rushdie's The Satanic Verses. Then, the "ideology" concept of this thesis is defined: not just the specific thought system of a group but a curriculum ofpower and conpol with its apparatuses, aims, directions, financial resources and political aspect. Different dimensions of ideology, which make it a curriculum, are also analyzed: the ideology of the author, the ideology of the translator(s), the ideology of institutions, the ideology of countries, the ideology of concepts and the ideology of theories. Ideology with all of its dimensions can affect the very first movement of translation and try to repress or even abort a text-to-be-translated. Thus, this thesis focuses on the place of selection, repression1 abortion and ideology in translation theory. The third chapter of this thesis analyzes the repression and abortion of The Satanic Verses both in the world and in Turkey to make concrete the ideas in the theoretical framework.
Keywords: Translating and interpreting -- Political aspects.